Summary Record of Discussion Annual Plan 1987-88 All States/UTS - Planning Commission (Planning Commission, 1987)
A copy of the summary record of discussion held between Deputy Chairman/ Planning Commission and the Chief Minister of Andhra Pradesh on 8th January/ 1987 to finalise the Annual Plan 1987-88 of the State/is circulated herewith.
Planning Commission State Plan Division
Planning Commission State Plan Division